Prognostic value of cardiac troponin in chronic stable heart failure: a systematic review. Issue 24 (31st October 2012) - Nagarajan, Vijaiganesh; Hernandez, Adrian V; Tang, W H Wilson
Abstract : Context: Cardiac troponins have become the 'gold standard' for diagnosing myocardial infarction. Elevation of cardiac troponins is noted in patients with chronic stable heart failure, but comparative prognostic value of different assay types is not established. Objective: To perform a systematic review for investigating the prognostic value of the different types of cardiac troponins (including low and high sensitivity) in chronic stable heart failure. Data sources: Search of three databases, PubMed, The Cochrane Library and Web of Science, was made in April 2012. Study selection: All studies which provided information on prognosis based upon the baseline cardiac troponin elevation in chronic stable heart failure were included. Limits applied were adults, humans and English language. Data extraction: Two authors individually reviewed all studies and extracted data on patient and study characteristics along with primary and secondary outcomes. Results: 16 of the 365 papers from three databases were finally included for data analysis. Elevated baseline cardiac troponin in patients with chronic stable heart failure was associated with a high risk of mortality (HR 2.85; 95% CI 2.02 to 4.03) and combined adverse cardiovascular outcome (HR 2.38; 95% CI 1.63 to 3.49). Although high-sensitivity assay detected cardiac troponin in higher proportion of patients compared with low-sensitivity assay, there was no statistically significant difference among both groups (p=0.54). Conclusions: Elevated baseline cardiac troponin level identified chronic stable heart failure patients who are at a higher risk of mortality and combined adverse cardiovascular outcomes. There was no statistically significant difference between high- and low-sensitivity cardiac troponins.